(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
In society there is a problem of inequality and gender violence where the school should be a space for deconstructing stereotypes and gender violence, empowering the new generations with an environment of diversity, breaking with unequal patterns. For this reason, the purpose of this presentation is to answer the following questions: What are the educational policies that schools at the basic primary, basic secondary and secondary level manage to avoid gender violence? aiming to explore and recognize the different methodologies addressed within the academic campus and at the same time understand the trajectory of public policies from gender equality within educational institutions through a bibliographic review to determine equality and prevention policies. of gender violence within educational institutions.